Optimized Control of Energy Flow in an Electric Vehicle based on GPS - Matúš Danko; Branislav Hanko; Peter Drgoňa (Communications - Scientific letters of the University of Zilina, 2021)
Presented paper deals with energy flow control of an electric vehicle with multiple energy storages. For efficiency control of energy flow is necessary to know the traction profile of the route. The Global Positioning System is used for observation of the traction profile. The first of the proposed algorithms uses the whole traction profile of a predetermined route, so the control algorithm can determine when the use of energy of the secondary energy storage is useful. The second proposed algorithm uses the GPS to determine the traction profile from routes stored in memory. If the route is not predetermined, or found in the memory of stored routes, the last algorithm controls the energy flow, based on the current of the primary energy storage. For verification of the proposed algorithm for control of the DC/DC converter, motor with inverter was replaced by the programmable power supply and programmable electronic load. The final evaluation shows that the proposed algorithm with the predetermined route saves about 5% more energy than the basic algorithm based on the battery current.